2008
DOI: 10.1136/ard.2006.068882
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of the effect of chondroitin sulphate on osteoarthritis articular tissues

Abstract: Osteoarthritis is a chronic disease characterised by irreversible damage to joint structures, including loss of articular cartilage, osteophyte formation, alterations in the subchondral bone and synovial inflammation. Pain, functional disability and impairment of health-related quality of life are major complaints in patients with osteoarthritis. Several compounds have been investigated for their positive effects on the relief of clinical symptoms and improvement of structural changes in osteoarthritis. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 67 publications
(38 reference statements)
2
75
0
7
Order By: Relevance
“…Use of CS for in Vitro Studies-Although the oral bioavailability of CS is acceptable (15-24%), ϳ90% is depolymerized or degraded either in plasma or the joints (7,30). Many in vitro studies have used high and variable concentrations of CS, ranging from 12.5 to 2000 g/ml but generally 200 g/ml or lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of CS for in Vitro Studies-Although the oral bioavailability of CS is acceptable (15-24%), ϳ90% is depolymerized or degraded either in plasma or the joints (7,30). Many in vitro studies have used high and variable concentrations of CS, ranging from 12.5 to 2000 g/ml but generally 200 g/ml or lower.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly evident because, in general, only CS has been investigated for effects in vitro, and virtually no information is available on the mixture of depolymerized or degradation products that are known to exist in inflamed joints (31). Nevertheless, these in vitro investigations (principally using chondrocytes or cartilage explants of bovine or human origin) have provided insight into the likely actions of CS (7,24,30,(32)(33)(34)(35)(36), including increased synthesis of proteoglycan, hyaluronic acid, and aggregan, blockade of proteoglycan degradation by interleukin-1 and other pro-inflammatory cytokines and metalloproteinases, prevention of oxyradical formation, modulation of chondrocyte signaling pathways, control of apoptosis, and stress-or aging-related changes in regeneration or repair (36). Thus, it can be summarized that CS has inhibitory effects on multiple cartilage catabolic reactions while also enhancing anabolic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35]. Подавляет преждевременную гибель (апоптоз) хондроцитов [36], а также подавляет биосинтез ИЛ 1β и дру-гих медиаторов воспаления [37][38][39]. Улучшает микроцир-куляцию в субхондральной кости и синовиальной ткани.…”
Section: гбоу впо «рязанский государственный медицинский университет unclassified
“…What is more, considering the slow acting effect of the drug in humans, the in vitro and in vivo systems were used for quite short durations. Different authors have suggested that the high concentration used in vitro was used to compensate these concerns [Tat et al 2010;Monfort et al 2008b]. Differences in the purity and properties of CS could be responsible for the disparity of the effects.…”
Section: Anti-oxidant Effectmentioning
confidence: 99%